Rare Case of Metastatic Cholangiocarcinoma leading to Panhypopituitarism - Emilia Surzyn; Sathyanarayana Machani (Internal Medicine, 2023)
Metastasis is a common complication of malignancy, however, researchers are constantly investigating and trying to better understand the way and pattern in which cancer spreads. Neuro-ophthalmologic and ocular presentations are rare in cholangiocarcinoma, with only one known confirmed case reported in 2020. This case features a patient with a known diagnosis of cholangiocarcinoma with bone metastasis; complicated by newly discovered subdural hematoma and suspected pituitary metastasis; with radiological evidence of abnormally large and enhancing pituitary, clinical features of left-sided cranial nerve 6th palsy and laboratory features of panhypopituitarism.